2021
DOI: 10.1007/s40801-021-00277-0
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter-2 Inhibitor Use is Associated with a Reduced Risk of Heart Failure Hospitalization in Patients with Heart Failure with Preserved Ejection Fraction and Type 2 Diabetes Mellitus: A Real-World Study on a Diverse Urban Population

Abstract: Background Limited evidence-based therapies exist for the management of heart failure with preserved ejection fraction (HFpEF). Sodium-glucose cotransporter-2 inhibitor (SGLT2i) use in patients with systolic heart failure (HFrEF) and type-2-diabetes mellitus (T2DM) is associated with improved cardiovascular (CV) and renal outcomes. Objective We sought to examine whether there is an association of SGLT2i use with improved CV outcomes in patients with HFpEF. Patients and methodsWe conducted a single-center, retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“… 44‐47 Importantly, these studies used an active comparator design. Thus, SGLT2 inhibitor initiators were at lower risk of ACHA compared with initiators of other GLAs, mainly dipeptidyl peptidase‐4 (DPP‐4) inhibitors 44‐47 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 44‐47 Importantly, these studies used an active comparator design. Thus, SGLT2 inhibitor initiators were at lower risk of ACHA compared with initiators of other GLAs, mainly dipeptidyl peptidase‐4 (DPP‐4) inhibitors 44‐47 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SGLT2 inhibitor use in real‐world settings was associated with reductions in the number of emergency room and outpatient visits ( Table 1 ). 44‐47 Importantly, these studies used an active comparator design. Thus, SGLT2 inhibitor initiators were at lower risk of ACHA compared with initiators of other GLAs, mainly dipeptidyl peptidase‐4 (DPP‐4) inhibitors 44‐47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was stopped earlier than planned, but SOLOIST-WHF for the first time in the randomised controlled trial (RCT) demonstrated a reduction in major combined endpoints such as HF hospitalisations+cardiovascular death+urgent visits for worsening HF 45. Li et al showed that the use of SGLT2i was associated with a decrease in HHF, and the incidence of AKI in patients with HFpEF and TD2M 46. The possible beneficial effect of SGLT2i in HFpEF can be judged on the basis of the results of the EMPA-REG OUTCOME study, which evaluated the effectiveness of empagliflozin in patients with TD2M, with or without a reported history of HF.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Li et al showed that the use of SGLT2i was associated with a decrease in HHF, and the incidence of AKI in patients with HFpEF and TD2M. 46 The possible beneficial effect of SGLT2i in HFpEF can be judged on the basis of the results of the EMPA-REG OUTCOME study, which evaluated the effectiveness of empagliflozin in patients with TD2M, with or without a reported history of HF. A predictive method was applied to the population in this trail, 47 according to which empagliflozin was shown to decrease mortality and HF hospitalisations, regardless of LVEF.…”
Section: Discussionmentioning
confidence: 99%